THE EFFECT OF HIGH-INTENSITY INTERVAL TRAINING, MODERATE-INTENSITY INTERVAL TRAINING, AND CONTINUOUS TRAINING ON ANAEROBIC AND AEROBIC CAPACITY - Tun, Han; Kanchanathaweekul, Thawatchai; Hongsaenyatham, Prakit (วารสารพุทธปรัชญาวิวัฒน์, 2022)
The purpose of this research is to study and compare the effects of high-intensity interval training (HIIT), moderate-intensity interval training (MIIT), and continuous training (CT) on anaerobic and aerobic capacity in Bangkokthonburi university students. Methods: 21 male students aged 20-24 years who are now studying in the Faculty of Sports Science and Technology of Bangkokthonburi university volunteered to participate in this study. Subjects were divided into 3 groups of 7 subjects who participated in 8 weeks of exercise training for 3 days/per week. The HIIT group (n=7) conducted a 20-second sprint exercise with 45 seconds of walking for 5 sets. The MIIT group performed 4 minutes of moderate-intensity running exercise alternating 4 minutes of walking for 4 sets, and the CT group performed 45 minutes of continuous running exercise training with pre and post-test. Data were analyzed with statistics mean, and standard deviation. Differentiated by one-way ANOVA and Tukey's test. Results: Anaerobic capacity; HIIT (7.67±0.76 W.kg -1 ) was indifferent from MIIT (8.06±0.70 W.kg -1 ) (p>0.05) but significant difference from CT (7.81±0.54 W.kg -1 ) (p<0.05) while the aerobic capacity for HIIT (3.81±0.441 ml/kg/min) was indifferent from MIIT (3.95±0.39 ml/kg/min) (p>0.05), but HIIT (3.81±0.441 ml/kg/min) was significant difference from CT (4.42±0.72 ml/kg/min) (p<0.05).